A Wide-Angle and Polarization-Insensitive Rectifying Metasurface for 5.8 GHz RF Energy Harvesting - Zhihui Guo; Juan Yu; Lin Dong (Micromachines)
This paper presents a rectifying metasurface (RMS) that enables wide-angle, polarization-insensitive wireless energy harvesting in the Wi-Fi frequency range. The RMS consists of a metasurface integrated with rectifying diodes, a low-pass filter (LPF), and a resistive load. In the structural design, the RMS incorporates four Schottky diodes placed on the bottom structure and connected to the top structure through four metallized vias. This configuration facilitates impedance matching between the metasurface and the diodes, omitting the need for conventional rectifier circuits or external matching networks and removing the impact of soldering variations. A 3 × 3 RMS prototype was manufactured and subjected to experimental validation. The measurements confirm that the RMS achieves a peak RF-to-DC conversion efficiency of 68.3% at 5.8 GHz with a 12.5 dBm input power, while maintaining stable performance across a wide range of incident angles and polarization states.